Implementation of lean construction in construction project towards safety improvement / Zalikha Morshidi - Morshidi, Zalikha (2020)
Occupational accidents are wasteful and inefficient in the construction work process and lean construction is a promising concept that has been extensively debated in the construction industry towards safety enhancement. The emergence of lean construction is seen as a positive approach that can be used to establish best practices and it is seen as a push to bring the construction sector to a more ideal degree of profitability with outstanding use of resources whilst delivering the most extreme value. Hence, the aim of this research is to ascertain the lean construction concepts and implementation towards safety improvement in construction projects. In order to achieve the aim of this research, the first objective is to study the concept of lean construction including its components towards safety and how it is applied in construction projects. Through literature review, it was found that lean construction is kwon to be the technique used to create opportunities for improving safety culture. The second objective is to identify the level of knowledge and apllication of lean construction towards safety in construction projects. A questionnaire survey was distributed to G7 contractors in Kuching, Sarawak, who are registered under the CIDB to obtain information. The result shows that most contractors are unaware of lean construction despite applying the tools in their construction projects as they are unfamiliar with the terminologies. Additionally, the third objective is to determine factors that hinder the implementation of lean construction in construction site in which the data was gathered through a questionnaire survey as well. A significant number of respondents agree that lack of awareness is causing the slow implementation of lean construction in construction projects despite its benefits towards safety enhancement. In summary, it is expected that this study can improve the awareness and implementation of lean construction in any organisation or workplace.